PENGARUH KERAGAMAN PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO LARISHI KOTA BIMA - Femi Sayid Datun Nisa; Ita Purnama; Mulyadin (Universitas Mahendradatta, 2025)
This research aims to determine the influence of product diversity and price onpurchasing decisions for Larishi figures in Bima City. The Larishi figure whose address isJl. Soekarno Hatta, Monggonao, District. Mpunda, Kab. Bima, West Nusa Tenggara.84117. This research is associative type using primary data sources. This researchinstrument uses a Likert scale questionnaire with the research population including allconsumers from the Larishi Store. The exact number is not known, to determine the numberof samples in an unknown population, the Unknown Population formula was used and asample of 96 people was obtained. The sampling technique used was purposive sampling. Inthis research, the data collection techniques used by researchers were observation,questionnaires and literature study. Researchers use analytical tools for validity tests,reliability tests, classical assumption tests, multiple linear regression, multiple correlationcoefficients, determination tests, t tests and f tests.The results of the research show that there is a significant influence between productdiversity on purchasing decisions at the Larishi shop in Bima City in Accept. There is asignificant influence between price on purchasing decisions at the Larishi shop in BimaCity in Accept. There is a simultaneous influence of product diversity and price onpurchasing decisions at the Larishi Shop in Bima City.